DIFFERENCE IN BODY'S DYNAMIC BALANCE BEFORE AND AFTER CONDUCTING CIRCUIT TRAINING OF STUDENTS AT MEDICAL FACULTY OF DIPONEGORO UNIVERSITY - Kusumaningtyas Ayu Amarihati; Yosef Purwoko; Ferdy Kurniawan Cayami; Endang Kumaidah (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2020)
Background: Physical inactivity that happens recently increase the risk of various disease. Circuit training is an exercise that can be completed with a short amount of time and has varied movements. With circuit training, subject expected to have increase in physical fitness in the body’s dynamic balance. The purpose of this study to find out whether circuit training can produce different scores of the body’s dynamic balance of students at medical Faculty of Diponegoro University. Methods: This study used a quasi-experimental design with pre-test and post-test comparison group. The subjects were from the Medical Faculty of Diponegoro University (n = 46) which were divided into control group and treatment group. The treatment group (n = 24) was given circuit training for 6 weeks with increased number of circuits for every 2 weeks, while the control group (n = 22) carried out activities as usual without doing any sports. The measuring of body's dynamic balance was carried out before starting circuit training and after completing 6 weeks of circuit training. Data were collected and then analyzed using the unpaired T-test and the paired T-test for normally distributed data. Meanwhile, the Mann-Whitney test and Wilcoxon test were used for non-normally distributed data. Results: The score of the body’s dynamic balance in the treatment group increased for the right leg with a pre-test score of 75.60 ± 13.74 to 95.75 ± 10.98. The balance score for the left leg also increased with the pre-test score of 78.05 ± 13.12 to 95.95 ± 10.33. The score of the difference between the post-test and pre-test of the treatment group of both legs has a significant value of (p = 0,000). Conclusion: Circuit training with increased number of circuits for every 2 weeks can increase the scores of the body’s dynamic balance of of students at medical faculty of Diponegoro University.Keywords: circuit training, body’s dynamic balance, Y balance test